Validity and reliability of the Clinical Learning Environment, Supervision and Nurse Teacher (CLES plus T), Turkish version - Atay S; Kurt FY; Aslan GK; Saarikoski M; Yilmaz H; Ekincr V (UNIV SAO PAULO, ESCOLA DE ENFERMAGEM DE RIBEIRAO PRETO, 2022)
Aim: A methodological type of study was conducted for the purpose of investigating the validity and reliability of the Turkish version of the Clinical Learning Environment, Supervision and Nurse Teacher (CLES+T) evaluation scale of the clinical learning environment of students, clinical nurses, and educators. Methods: Sample was comprised of 602 Turkish nursing students with clinical practice experience at the hospital. The CLES+T, developed by Saarikoski, was used for data collection. Language equivalency, internal consistency, item-total correlation, and structure validity were conducted within the scope of the validity and reliability study on the CLES +T scale. Results: It was determined that item-total correlations of four items were lower than 0.30, and those items were removed from the scale as a result of item analysis. The Cronbach's alpha value of the scale was 0.93-0.99; item total point correlations of the scale varied between 0.45 and 0.66; six factors were identified in the CLES+T factor analysis study, with a total variance explained by these six factors of 64%. Conclusion: According to the findings of the research, the CLES+T Turkish version was found to be a valid and reliable scale, which can be used to evaluate satisfaction of nursing students with their clinical education in Turkey.